2018
DOI: 10.1002/ana.25284
|View full text |Cite
|
Sign up to set email alerts
|

Notch3ECD immunotherapy improves cerebrovascular responses in CADASIL mice

Abstract: This study establishes immunotherapy targeting Notch3 as a new avenue for disease-modifying treatment in CADASIL that warrants further development. Ann Neurol 2018;84:246-259.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…One solution has been the introduction of therapeutic monoclonal antibodies specific to Notch3, providing a strategy to down-regulate activity of Notch3. Monoclonal Notch3 antibody treatment has already been tested in experimental models of CADASIL, where treatment was shown to improve cerebrovascular function in the TgN3 R169C CADASIL mouse model [139], which has a gain of function of Notch3 [140]. Studies are now exploring potential therapeutic use of monoclonal antibodies for PAH.…”
Section: Notch3 Inhibition As a Potential Therapeutic Target In Pulmomentioning
confidence: 99%
“…One solution has been the introduction of therapeutic monoclonal antibodies specific to Notch3, providing a strategy to down-regulate activity of Notch3. Monoclonal Notch3 antibody treatment has already been tested in experimental models of CADASIL, where treatment was shown to improve cerebrovascular function in the TgN3 R169C CADASIL mouse model [139], which has a gain of function of Notch3 [140]. Studies are now exploring potential therapeutic use of monoclonal antibodies for PAH.…”
Section: Notch3 Inhibition As a Potential Therapeutic Target In Pulmomentioning
confidence: 99%
“…In that study, intraperitoneal injections of 5E1 in transgenic mice showed that 5E1 clone could detect NOTCH3-ECD deposits, but failed to reduce NOTCH3-ECD/GOM deposition. However, 5E1 injection had beneficial effects on cerebrovascular function by normalizing vasodilatory responses and myogenic tone (Ghezali et al, 2018). The evidence that peripheral immunotherapy targeting NOTCH3-ECD protects against cerebrovascular dysfunction despite continued NOTCH3-ECD accumulation/GOM deposition might challenge the concept of proteins accumulation as the driving force in CADASIL, emphasizing the role of other possible mechanism, such as cerebrovascular flow hemodynamics, in the pathogenesis of the disease (Ghezali et al, 2018).…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…The evidence that peripheral immunotherapy targeting NOTCH3-ECD protects against cerebrovascular dysfunction despite continued NOTCH3-ECD accumulation/GOM deposition might challenge the concept of proteins accumulation as the driving force in CADASIL, emphasizing the role of other possible mechanism, such as cerebrovascular flow hemodynamics, in the pathogenesis of the disease (Ghezali et al, 2018). More studies are required to determine if this approach could have beneficial effects in CADASIL patients (Ghezali et al, 2018).…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…However, the consequences of agonist antibodies were not investigated on more archetypal, N-terminally located, CADASIL mutants that have been reported not to have Notch signalling deficits. An alternative approach targeting the proposed toxic effect of Notch3 aggregates has also been tested using an antibody against the Notch EGF module-containing region of the ECD [104]. The aggregates in the mouse transgenic CADASIL model were successfully decorated with the antibody and some reversal of impaired cerebral blood flow responses were also achieved.…”
Section: Notch3 and Cerebral Autosomal Dominant Arteriopathy With Submentioning
confidence: 99%